Synchronisation in the beta frequency-band--the bad boy of parkinsonism or an innocent bystander? - Eusebio, A; Brown, P (2009)
Excessive synchronisation of basal ganglia neuronal activity in the beta frequency band has been implicated in Parkinson's disease. In a recent issue of Experimental Neurology, Bronte-Stewart, H., Barberini, C., Koop, M.M., Hill, B.C., Henderson, J.M., Wingeier, B., 2009. The STN beta-band profile in Parkinson's disease is stationary and shows prolonged attenuation after deep brain stimulation. Exp. Neurol. 215, 20-28. demonstrate that such activity is consistent over time and provide further evidence that deep brain stimulation is associated with its suppression. However, the extent to which beta synchrony has a mechanistic (rather than epiphenomenal) role in parkinsonism remains unclear, and the suppression of this activity by deep brain stimulation is contentious. This commentary discusses the evidence for and against a role for excessive beta synchrony in mediating the parkinsonian phenotype and in providing a possible mechanism to explain the therapeutic effects of deep brain stimulation in Parkinson's disease.